Lessons learned and next steps for the CGIAR Initiative on One Health - Lam, Steven; Patel, Ekta; Hoffmann, Vivian; Bett, Bernard K.; Fèvre, Eric M.; Moodley, Arshnee; Rheman, S.; Mateo-Sagasta, J.; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
To reflect on lessons of the CGIAR Initiative on One Health (2022–24)and plan for the future, a one-day workshop was held in Cape Town on 19 September 2024, ahead of the 8th World One Health Congress. The event gathered 33 participants, including researchers and partners of the initiative.